(untitled) (Journal of Governance and Development (JGD), 2025)
This article discusses green innovation in post-tin mining land management in Jelutung Village, Bangka Belitung. The long-standing illegal mining in this area has caused significant environmental damage, leading to numerous abandoned mining pits. The innovation "Abang Timah Untuk Budisa" was launched to revitalize these lands through rice cultivation. This program aims not only to address land degradation issues but also to enhance local food security. This study employs a descriptive qualitative method, focusing on the policy implementation process using Edward III’s analysis theory. The results indicate that this innovation can meet the food needs of some residents of Jelutung Village and help fill some of the abandoned mining pits. Challenges faced during the implementation of this innovation included limited availability of fertilizers and agricultural facilities, which were addressed by utilizing manure and other management techniques. Overall, the "Abang Timah Untuk Budisa" innovation successfully transformed the former mining lands into productive areas, supported food security, and provided economic benefits to the community. This study employs a qualitative method because the problem presents a general description of the issue, along with a proposed solution. The conclusion is that the problem is about preserving the environment for future generations, so everyone must strive to maintain it. This innovation has also gained national recognition, receiving awards from Menpan RB and Mendagri as one of the top 45 innovations in Indonesia.